Pengaruh Kualitas Layanan Dan Kepercayaan Terhadap Keputusan Memilih Sekolah Melalui Kepuasan Orangtua Di Smp Strada Budi Luhur Kota Bekasi - Adestyani, Erminia; Rachmawati, Ike Kusdyah; Handoko, Yunus (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
The ability of a country to progress and develop is highly dependent on its level of education. The mentality of the young generation is increasing rapidly through both formal and informal education. The importance of education has driven the growth of the education sector, which is now a major industry and even a separate business sector. When a business in the education sector is established, the competition is to win the hearts of parents and convince them to enroll their children in the school. Through parental satisfaction at SMP Strada Budi Luhur, Bekasi City, this study aims to analyze the influence of service quality and trust on the decision to choose a school. Path analysis combined with quantitative methods was used in this study. The sample consisted of 223 parents selected using random sampling techniques. The results of the study showed that: (1) There is a direct and significant relationship between service quality and parental decisions; (2) There is a direct and significant relationship between trust and satisfaction; (3) There is a direct and significant relationship between service quality and parental decisions; (4) There is a direct and significant relationship between trust and parental decisions; (5) There is a direct and significant relationship between satisfaction and parental decisions; (6) There is a direct and significant influence between service quality and parental decisions mediated by satisfaction as an intervening variable; (7) There is a direct and significant relationship between service quality and parents' decisions. Keyword: Service Quality, Trust, Satisfaction, Parents' DecisionsResource Quality